A Qualitative Systematic Review of Effects of Provider Characteristics and Nonverbal Behavior on Pain, and Placebo and Nocebo Effects - Daniali, Hojjat; Flaten, Magne Arve (Frontiers in Psychiatry, 2019)
Background: Previous research has indicated that the sex, status, and nonverbal behaviors of experimenters or clinicians can contribute to reported pain, and placebo and nocebo effects in patients or research participants. However, no systematic review has been published. Objective: The aim of this study was to investigate the effects of experimenter/clinician characteristics and nonverbal behavior on pain, placebo, and nocebo effects. Methods: Using EmBase, Web of Knowledge, and PubMed databases, several literature searches were conducted to find studies that investigated the effects of the experimenter’s/clinician’s sex, status, and nonverbal behaviors on pain, placebo, and nocebo effects. Results: Thirty-four studies were included, 20 on the effects of characteristics of the experimenter/clinician, 11 on the role of nonverbal behaviors, and 3 on the effects of both nonverbal behaviors and characteristics of experimenters/clinicians on pain and placebo/nocebo effects. There was a tendency for experimenters/clinicians to induce lower pain report in participants of the opposite sex. Furthermore, higher confidence, competence, and professionalism of experimenters/clinicians resulted in lower pain report and higher placebo effects, whereas lower status of experimenters/clinicians such as lower confidence, competence, and professionalism generated higher reported pain and lower placebo effects. Positive nonverbal behaviors (e.g., smiling, strong tone of voice, more eye contact, more leaning toward the patient/participant, and more body gestures) contributed to lower reported pain and higher placebo effects, whereas negative nonverbal behaviors (i.e., no smile, monotonous tone of voice, no eye contact, leaning backward from the participant/patient, and no body gestures) contributed to higher reported pain and nocebo effects. Conclusion: Characteristics and nonverbal behaviors of experimenters/clinicians contribute to the elicitation and modulation of pain, placebo, and nocebo effects.